Diversity in perception and management of farming risks in southern Mali. (September 2020) - Huet, E.K.; Adam, M.; Giller, K.E.; Descheemaeker, K.
Abstract: A deeper understanding of how smallholder farmers perceive and manage risks is crucial to identify options that increase farmers' adaptive capacity. We investigated a broad range of risks that play a role in farmers' decision-making processes. In the cotton zone of Mali opportunities and constraints vary with the resource endowment of farms. Furthermore, as households are large in this region, often comprising 20–50 family members, intra-household diversity may influence perceptions and risk management. For this reason, we analysed diversity both among and within farms. Information was gathered through focus group discussions and a survey with 250 people from 58 households. Risk was assessed as the combination of the perceived frequency of occurrence of hazards and the impact on food availability and income. Farmers faced a diversity of risks, with hazards related to animal and personal health, and climate variability of highest concern. Resource endowment of farms was related to risk perception to a limited extent. Differences within the household were related to the generational factor and decision power, and not to gender. Household members with decision power worried most about risks. Almost a quarter of described hazards occurred with a high frequency and led to a high impact on food availability and income. Low resource-endowed farms were more often exposed to high risks than other farm types. Farmers applied a variety of actions to cope with hazards, yet in many cases farmers lacked a response. Medical actions were targeted to human and animal health hazards. Changes in field and animal management practices, adapted consumption rates and calls on social interactions, were combined for a diversity of hazards. By assessing the diversity of risks encountered by farmers and the diversity of risk management actions taken by farmers, this study goes beyond common risk research that focuses on a single hazard. Our results suggest that development interventions should not focus on either agronomic or economic options separately, but combine both to strengthen social well-being and agricultural production. Highlights: West-African farmers deal with many risks in addition to risks related to climate variability. Within households, differences in risk perception are related to decision power; not to gender. Farmers manage risks by diversification and overcome losses by using productive assets.